Beer and obesity: a cross-sectional study - Bobak, M; Skodova, Z; Marmot, M (European journal of clinical nutrition, 2003)
OBJECTIVE: There is a common notion that beer drinkers are, on average, more 'obese' than either nondrinkers or drinkers of wine or spirits. This is reflected, for example, by the expression 'beer belly'. However, the few studies on the association between consumption of beer and abdominal obesity produced inconsistent results. We examined the relation between beer intake and waist-hip ratio (WHR) and body mass index (BMI) in a beer-drinking population. DESIGN: A cross-sectional study. SETTINGS: General population of six districts of the Czech Republic. SUBJECTS: A random sample of 1141 men and 1212 women aged 25-64 y (response rate 76%) completed a questionnaire and underwent a short examination in a clinic. Intake of beer, wine and spirits during a typical week, frequency of drinking, and a number of other factors were measured by a questionnaire. The present analyses are based on 891 men and 1098 women who where either nondrinkers or 'exclusive' beer drinkers (ie they did not drink any wine or spirits in a typical week). RESULTS: The mean weekly beer intake was 3.1 l in men and 0.3 l in women. In men, beer intake was positively related to WHR in age-adjusted analyses, but the association was attenuated and became nonsignificant after controlling for other risk factors. There appeared to be an interaction with smoking: the relation between beer intake and WHR was seen only among nonsmokers. Beer intake was not related to BMI in men. In women, beer intake was not related to WHR, but there was a weak inverse association with BMI. CONCLUSION: It is unlikely that beer intake is associated with a largely increased WHR or BMI.
Keywords: kouření; průřezové studie; víno; obezita; Body Constitution; Alcoholic Beverages; Cross-Sectional Studies; Abdomen; pivo; Česká republika; lidé; Wine; tělesná konstituce; Smoking; index tělesné hmotnosti; Beer; Czech Republic; mužské pohlaví; Alcohol Drinking; Female; Adult; Surveys and Questionnaires; Obesity; Male; průzkumy a dotazníky; pití alkoholu; dospělí; ženské pohlaví; alkoholické nápoje; Humans; lidé středního věku; Middle Aged; Body Mass Index; břicho